NF1 Gene Novel Splicing Mutations in a Chinese Family with Neurofibromatosis Type 1: Case Series - Wu T; Yang H; Xu L; Huang Q; He Q; Wu R; Mu YZ (Dove Medical Press, 2022)
Ting Wu,1,* Hao Yang,1,* Liuli Xu,1 Qing Huang,1 Qi He,1 Rong Wu,2 Yun-Zhu Mu1 1Department of Dermatology, the Affiliated Hospital of North Sichuan Medical College, Nanchong, People's Republic of China; 2Pediatric department, Women's and Children's hospital of GaoPing District, Nanchong, People's Republic of China*These authors contributed equally to this workCorrespondence: Yun-Zhu Mu, Department of Dermatology, the Affiliated Hospital of North Sichuan Medical College, No. 1 Maoyuan South Road, Shunqing District, Nanchong, Sichuan Province, 63700, People's Republic of China, Tel +8615984833231, Email hymyz77@163.comBackground: Neurofibromatosis type 1 (NF1) is a common autosomal dominant genetic disorder. NF1 is a multisystemic disease and its pathogenesis involves mutations in the NF1 gene on chromosome 17q11.2 causing RAS overactivation to stimulate abnormal cell proliferation.Purpose: To identify pathogenic mutation of the NF1 gene in a pedigree of NF1.Patients and Methods: Collection of clinical data from one NF1 family. Peripheral blood samples were collected from the affected persons and their family members. Potential mutations of NF1 gene were screened by exome and cDNA sequencing.Results: A splice mutation (c.4836- 10T>G) was found in exon 37 of the NF1 gene in this NFI family, and no corresponding mutation was found in healthy members of this pedigree or in the human reference genome (GRCh37/hg19).Conclusion: Mutations of NF1 gene is a major cause of NF1. The novel splice mutation in exon 37 of NF1 gene is the underlying cause of the familial c.4836- 10T>G.Keywords: neurofibromatosis type 1, gene, splicing mutation, sequencing